Genetic Alterations in War-Related Post-Traumatic Stress Disorder: A Systematic Review - Amir Hossein Rajabi; Samaneh Zafarabadi; Kimia Jazi; Maryam Moghbel Baerz; Omid Bahrami; Gelareh Azarinoush; Pardis Habibi; Negar Azami; Shahram Paydar (Bulletin of Emergency and Trauma)
Objectives: This systematic review explored gene expression and DNA methylation patterns to identify key pathways and molecular targets associated with post-traumatic stress disorder (PTSD), particularly its war-related subtype.Methods: A comprehensive search of PubMed, Scopus, and Web of Science was conducted using keywords related to PTSD, gene expression, and DNA methylation. Studies published between 2000 to 2024 involving adult military personnel with confirmed PTSD based on the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5) criteria were included. Animal studies, psychological interventions, and pharmacological research were excluded. Only cross-sectional, case-control, or cohort studies utilizing blood, saliva, or brain tissue samples were considered. Data from 28 studies were extracted using a predefined framework, focusing on population characteristics, study design, and identified hub genes.Results: Key findings revealed the upregulation of immune-related genes (e.g., CCL4, NF-κB) and hypomethylation of inflammation-related genes. Downregulation of neurodevelopmental genes, such as Brain-Derived Neurotropic Factor (BDNF) and Down syndrome cell adhesion molecule (DSCAM), highlighted disruptions in synaptic plasticity. The identified pathways suggested potential biomarkers and therapeutic targets for precision medicine approaches.Conclusion: This review highlighted the role of gene expression alterations in war-related PTSD. The identified genes might serve as candidates for personalized therapies. Further research is required to validate these findings and develop targeted interventions.